1975
DOI: 10.1542/peds.55.2.191
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Malignant Melanoma in Prepubertal Children

Abstract: Medical literature is full of involved and Confusing reports on the genesis, incidence, and development of metastatic melanoma in children. The reason for this confusion can be found in the early uncertainties that surrounded the real nature and correct diagnosis of metastatic melanoma in the prepubertal child. Before 1950, reports of melanomas with metastases in children were rare, poorly documented, and in many cases erroneous.1-4 In particular, benign nevi (now known as benign juvenile melanoma) went unreco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Melanoma arising from GCN has a worse prognosis than melanoma that arises elsewhere 4 . Trozak et al 16 performed a literature review of pediatric melanoma and found that none of 20 children whose tumors were associated with a GCN were alive after 5 years. This is attributed to melanoma in these lesions arising in the deeper dermis, 4,11 which makes early detection difficult and early spread by lymphatic or blood vessels more likely 4 …”
Section: Discussionmentioning
confidence: 99%
“…Melanoma arising from GCN has a worse prognosis than melanoma that arises elsewhere 4 . Trozak et al 16 performed a literature review of pediatric melanoma and found that none of 20 children whose tumors were associated with a GCN were alive after 5 years. This is attributed to melanoma in these lesions arising in the deeper dermis, 4,11 which makes early detection difficult and early spread by lymphatic or blood vessels more likely 4 …”
Section: Discussionmentioning
confidence: 99%
“…The deeper location also facilitates earlier spread through lymphoid vessels and blood vessels of greater calibre, leading to early metastasis. 45 In 24% of cases, the melanoma has already metastases at the time of the diagnosis. 44 One out of three melanomas develop primarily in the CNS in these patients, hence removing the CMN does not prevent the risk of death due to melanoma.…”
Section: Melanoma Risk In Congenital Melanocytic Naevimentioning
confidence: 99%
“…Rapid change and ulceration in congenital naevus are markers for the melanoma development 14,47 . Additionally, the rough, hairy, nodular surface of CMN masks the early observation of the tumour 45 …”
Section: Melanoma Risk In Congenital Melanocytic Naevimentioning
confidence: 99%
See 2 more Smart Citations